Clinical and Experimental Advances in Regeneration of Spinal Cord Injury. (20th October 2010) - Hyun, Jung Keun; Kim, Hae-Won
Abstract : Spinal cord injury (SCI) is one of the major disabilities dealt with in clinical rehabilitation settings and is multifactorial in that the patients suffer from motor and sensory impairments as well as many other complications throughout their lifetimes. Many clinical trials have been documented during the last two decades to restore damaged spinal cords. However, only a few pharmacological therapies used in clinical settings which still have only limited effects on the regeneration, recovery speed, or retraining of the spinal cord. In this paper, we will introduce recent clinical trials, which performed pharmacological treatments and cell transplantations for patients with SCI, and evaluate recent in vivo studies for the regeneration of injured spinal cord, including stem-cell transplantation, application of neurotrophic factors and suppressor of inhibiting factors, development of biomaterial scaffolds and delivery systems, rehabilitation, and the combinations of these therapies to evaluate what can be appropriately applied in the future to the patients with SCI.